2021
DOI: 10.3390/cancers13061404
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast-Enhanced MRI of Prostate Lesions of Simultaneous [68Ga]Ga-PSMA-11 PET/MRI: Comparison between Intraprostatic Lesions and Correlation between Perfusion Parameters

Abstract: We aimed to retrospectively compare the perfusion parameters measured from dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) of prostate benign lesions and malignant lesions to determine the relationship between perfusion parameters. DCE-MRI was performed in patients with PCa who underwent simultaneous [68Ga]Ga-prostate-specific membrane antigen (PSMA)-11 positron emission tomography (PET)/MRI. Six perfusion parameters (arrival time (AT), time to peak (TTP), wash-in slope (W-in), wash-out slope … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Although no strict guidelines could be driven from this study, we showed that, globally, the Tmax, and max slope volume improved detection sensitivity of CS and GS PCa lesions. This is concordant with other studies where the Tmax was found to have a significant impact on the detection of PCa lesions [14]. The mid fusion strategy seems to be beneficial both in terms of detection sensitivity and prostate segmentation.…”
Section: Discussionsupporting
confidence: 91%
“…Although no strict guidelines could be driven from this study, we showed that, globally, the Tmax, and max slope volume improved detection sensitivity of CS and GS PCa lesions. This is concordant with other studies where the Tmax was found to have a significant impact on the detection of PCa lesions [14]. The mid fusion strategy seems to be beneficial both in terms of detection sensitivity and prostate segmentation.…”
Section: Discussionsupporting
confidence: 91%
“…Elastin is a cross-linked polymer whose cross-linking is difficult to break. Before cross-linking, the soluble precursor tropoelastin forms self-associated aggregates (coacervation) after expression [ 15 ]. Only these non-cross-linked aggregates can be broken down back into the small soluble tropoelastin proteins that can be detected in the Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…To further improve tissue differentiation, molecular probes could be used as opposed to the currently available unspecific extracellular Gd-based contrast agents [ 15 ]. In addition, molecular imaging could be used as an added tool to current diagnostic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] In particular, qualitative and semi-quantitative analyses are used to evaluate the temporal changes of contrast agent flows or perfusion within tumors, which can be visualized by a time-intensity curve (TIC). 24 TICs derived from DCE images can be divided into three patterns of wash-out phase within the tumor, that is, progressive, plateau, and wash-out patterns, which might be related to malignancy, 18 but the curves showed poor differentiation of prostate cancer from healthy prostatic tissue. 25 Therefore, in this study, we proposed two-dimensional (2D) joint histograms between different phases of DCE or subtraction phases of DCE (SPD) images for the visualization of temporally changing perfusion patterns in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There are qualitative, semi‐quantitative, and quantitative approaches for analyzing DCE images 19–23 . In particular, qualitative and semi‐quantitative analyses are used to evaluate the temporal changes of contrast agent flows or perfusion within tumors, which can be visualized by a time‐intensity curve (TIC) 24 . TICs derived from DCE images can be divided into three patterns of wash‐out phase within the tumor, that is, progressive, plateau, and wash‐out patterns, which might be related to malignancy, 18 but the curves showed poor differentiation of prostate cancer from healthy prostatic tissue 25 …”
Section: Introductionmentioning
confidence: 99%